Analysis of Cutmarks on Bone: Can Light Microscopy Be of Any Help?. (December 2016) - Cerutti, Elisa; Spagnoli, Laura; Araujo, Nadezhda; Gibelli, Daniele; Mazzarelli, Debora; Cattaneo, Cristina
Abstract : Abstract: One of the main issues in forensic anthropology consists of the identification of signs of trauma in skeletal remains, including sharp-force injuries. So far, several studies have been performed to assess differences between injuries caused by different instruments, not, however, through light microscopy. In this study, 152 sharp-force injuries were performed by 5 different tools through 2 different orientations on 2 humeral diaphyses and were analyzed by stereo and light microscopy to assess possible morphological differences. This study showed that although W-shaped injuries are frequently reported in cases of wood-cutting saws, other shapes are often observed; lesions due to metal-cutting saws are almost always U shaped, whereas injuries caused by knives are V shaped. Although cut marks may represent a variable range of features, the present study was able to highlight typical profiles that may be of some help for the diagnosis of weapon and the intentionality of the action.